Impact of Service Quality and Product Quality on Customer Loyalty Through Customer Satisfaction on UMKM in the Field Kota Medan - Parapat Gultom; Cutserly Utari; Mawar Winda Manalu (TALENTA Publisher, Universitas Sumatera Utara, 2024)
This study aims to determine and analyze the effect of service quality and product quality on customer loyalty through customer satisfaction in MSMEs in Medan City, namely in the coffee shop business. The research method used is a survey with data collection techniques using an online questionnaire which obtained a sample of 100 respondents through judgment sampling. The data in this study were analyzed using SmartPLS software. The results showed that service quality has no significant effect on customer loyalty, product quality has a significant effect on customer loyalty, service quality has a significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction, customer satisfaction has a significant effect on customer loyalty, service quality through customer satisfaction has no significant effect on customer loyalty, product quality through customer satisfaction has a significant effect on customer loyalty.